Improving powertrain efficiency through torque modulation techniques in single and dual motor electric vehicles - Y. Xu; P. Ingelström; A. Kersten; A. Andersson; S. Klacar; S. George; D. Sedarsky (Transportation Engineering, 2024)
Battery Electric Vehicles (BEVs) typically experience reduced powertrain energy efficiency under low-torque operating conditions. This issue can be mitigated by torque modulation, i.e., alternating driver torque demand between zero and an appropriate value. This paper aims to maximize the efficiency improvement of torque modulation and investigate its potential in two powertrain topologies: single and dual motor powertrains. To this end, optimal modulation strategies are proposed for both powertrains, considering overall powertrain energy losses and specific powertrain characteristics. Additionally, the adverse impact on driver comfort and powertrain durability due to the pulsating torque is examined. The results suggest that the proposed optimal modulation strategies can enhance powertrain efficiency while maintaining acceptable levels of driver comfort and powertrain durability. In addition, complementary modulation and torque distribution can be applied in the dual motor powertrain to provide further energy-saving potential and reduced impact on driver comfort.